Isolation and Characterization of a Novel Escherichia Bacteriophage with Potential to Control Multidrug-Resistant Avian Pathogenic Escherichia coli and Biofilms - Phitchayapak Wintachai; Fahsai Thaion; Martha R. J. Clokie; Thotsapol Thomrongsuwannakij (MDPI AG, 2024)
Background/Objectives: Avian pathogenic Escherichia coli (APEC) infection is a significant problem for the global chicken industry, as it decreases animal welfare and is associated with substantial economic losses. Traditionally, APEC infections have been controlled through the use of antibiotics, which has led to an increased prevalence of antibiotic-resistant E. coli. Therefore, developing alternative treatments for APEC infection is crucial. Methods: In this study, an Escherichia phage specific to multidrug-resistant (MDR) APEC, designated as phage vB_EcoP_PW8 (phage vECPW8), was isolated. The morphology, phage adsorption to host cells, one-step growth curve, thermal stability, pH stability, whole-genome sequencing, antibacterial ability, and antibiofilm efficacy of phage vECPW8 were evaluated. Results: The results demonstrated that phage vECPW8 has a Podoviridae morphology and is effective at lysing bacteria. Phage vECPW8 exhibited a high absorption rate to bacterial cells (more than 85% within 10 min) and had a latent period of 20 min, with a burst size of 143 plaque-forming units per cell. Additionally, phage vECPW8 showed good temperature and pH stability. The phage displayed strong antibacterial activity in vitro, and its efficacy in controlling bacteria was confirmed through scanning electron microscopy. Whole-genome sequencing revealed that the phage has a linear genome with 69,579 base pairs. The genome analysis supported the safety of the phage, as no toxin, virulence, or resistance-related genes were detected. Phage vECPW8 was identified as a novel lytic phage in the Gamaleyavirus genus and Schitoviridae family. The phage also demonstrated antibiofilm efficacy by reducing and preventing biofilm formation, as evidenced by biofilm biomass and bacterial cell viability measurements. Conclusions: These results indicate that phage vECPW8 is a promising candidate for the effective treatment of MDR APEC infections in poultry.